Poor sitting posture and a heavy schoolbag as contributors to musculoskeletal pain in children: an ergonomic school education intervention program - Ismail, Syazwan Aizat; Mohd Noor, Mohamad Azhar; Abdul Rahman, Anita; H. S., Azizan; Mohd Sham, Shaharuddin; Juni, Muhamad Hanafiah; A. A., Muhaimin; A. M., Nizar; Baharudin, Mohd Rafee; Ardani, Mohd Ibthisham; Kasani, Adam (Dove Medical Press, 2011)
Objectives: The purpose of this study was to evaluate a multidisciplinary, interventional, ergonomic education program designed to reduce the risk of musculoskeletal problems by reducing schoolbag weight and correcting poor sitting posture. Methods: Data were collected twice before and twice following intervention using the Standardized Nordic Body Map Questionnaire, a rapid upper limb assessment for posture evaluation, and schoolbag weight measurement in children aged 8 and 11 years attending two schools within the central region of Malaysia. Results: Students who received the ergonomic intervention reported significant improvements in their sitting posture in a classroom environment and reduction of schoolbag weight as compared with the controls. Conclusion: A single-session, early intervention, group ergonomics education program for children aged 8 and 11 years is appropriate and effective, and should be considered as a strategy to reduce musculoskeletal pain among schoolchildren in this age group.